The Effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on Stock Prices of Technology Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the Period 2021–2023 - I Wayan Hara Jayate; Made Ayu Desy Geriadi; Ni Ketut Sukanti (Countable (Contemporary Business and Sustainability Science), 2025)
This study examines the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on stock prices of technology sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. The research uses a quantitative explanatory method, analyzing 87 firm-year observations obtained from 29 technology companies listed continuously on the IDX. Multiple linear regression was employed to test both partial and simultaneous effects, preceded by classical assumption tests to ensure data reliability. The results demonstrate that ROA and DER have a positive and statistically significant effect on stock prices both individually and jointly. Firms with higher profitability and optimal leverage tend to achieve stronger stock performance and higher investor confidence. The findings underline the importance of efficient asset utilization, balanced capital structures, and transparent communication with investors in stabilizing stock prices and enhancing corporate value.